2015
DOI: 10.1111/ajps.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Timeline of Elections: A Comparative Perspective

Abstract: How do voter preferences come into focus over the electoral cycle in different countries? Do they evolve in patterned ways? Does the evolution vary across countries? This article addresses these issues. We consider differences in political institutions and how they might impact voter preferences over the course of the election cycle. We then outline an empirical analysis relating support for parties or candidates in pre-election polls to their final vote. The analysis relies on over 26,000 vote intention polls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 48 publications
4
59
1
Order By: Relevance
“…As political information has been found to shape voters’ political perceptions and attitudes (e.g., Ladd & Lenz, 2009; Lazarsfeld et al, 1948; Lengauer & Johann, 2013; Schmitt-Beck, 2003), we argue that the individual’s information environment provides voters with important cues to make decisions and that it, consequently, has the ability to alter citizens’ voting preferences in the short term (e.g., Gerber & Green, 2000, Green & Gerber, 2015; Jennings & Wlezien, 2016; Karp & Banducci, 2007; van Spanje & de Vreese, 2014). We investigate the effect of communication efforts by the news media and political parties on short-term changes in voting preferences in the weeks before Election Day.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As political information has been found to shape voters’ political perceptions and attitudes (e.g., Ladd & Lenz, 2009; Lazarsfeld et al, 1948; Lengauer & Johann, 2013; Schmitt-Beck, 2003), we argue that the individual’s information environment provides voters with important cues to make decisions and that it, consequently, has the ability to alter citizens’ voting preferences in the short term (e.g., Gerber & Green, 2000, Green & Gerber, 2015; Jennings & Wlezien, 2016; Karp & Banducci, 2007; van Spanje & de Vreese, 2014). We investigate the effect of communication efforts by the news media and political parties on short-term changes in voting preferences in the weeks before Election Day.…”
Section: Introductionmentioning
confidence: 82%
“… 1 Electoral volatility has frequently been observed across countries and been addressed by a growing body of literature (e.g., Dassonneville, 2012; Jennings & Wlezien, 2016; Pedersen, 1979). Within this framework, inter-election vote switching is understood as a long-term process that predominantly affects the formation and evolution of party preferences (e.g., Hobolt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our measure of government popularity in the US is presidential approval, and voting intention for the governing party for the UK, Canada and Ireland (data from Jennings and Wlezien ; Green and Jennings forthcoming).…”
mentioning
confidence: 99%
“…Recent research on the causes of electoral volatility has also found evidence supporting this view of emancipated voters (Oscarsson 2016;Van der Meer et al 2015), although extant research is not conclusive (see below). Nevertheless, considering the decreasing impact of long-term factors on voting behavior, short-term factors, like election campaigns, have become more important for explaining vote choice (Dalton 1984(Dalton , 2000Geers, Bos, and De Vreese 2017;Jennings and Wlezien 2016;Johann et al 2017;Strömbäck 2016).…”
Section: Electoral Volatility: Types Of Changesmentioning
confidence: 99%